Crystal chemistry of the system Bi2O3-CdO-GeO2 - Wies, Stefan; Eysel, Walter (Powder diffraction, 1996)
The ternary phase diagram of the system Bi2O3-CdO-GeO2 was investigated in several isothermal sections using predominantly X-ray powder diffraction. The following phases are described with respect to their crystal chemistry, phase relations and powder patterns: Bi2−2xCd2x(O3−x⍽9+x) (solid solution with anti-α-AgI structure), CdGeO3 (complicated polymorphism), Bi12GeO20 (stoichiometric sillenite), Cd-sillenite (solid solution), Bi1.8Cd0.2GeO4.9 (metastable, new phase, new structure type with GeO5 polyhedra), Bi2CdGeO6 (new ternary oxide, new structure type).
Elektronische Reproduktion der Druck-Ausgabe 10. Januar 2013
Im Titel sind die Zahlen 2 und 3 tiefgestellt
Gesehen am 05.01.2023